Enhancing electrocatalytic nitrogen reduction to ammonia with rare earths (La, Y, and Sc) on high-index faceted platinum alloy concave nanocubes - Mao, Yu-Jie; Liu, Feng; Chen, You-Hu; Jiang, Xin; Zhao, Xin-Sheng; Sheng, Tian; Ye, Jin-Yu; Liao, Hong-Gang; Wei, Lu; Sun, Shi-Gang (Journal of materials chemistry. A, Materials for energy and sustainability, 2021)
Surface structure effect is the key subject in electrocatalysis, and consists of the structure dependence of interaction between reaction molecules and the catalyst surface in specifying the surface atomic arrangement, chemical composition and electronic structure. Herein, we develop a controllable synthesis of Pt-RE (RE = La, Y, Sc) alloy concave nanocubes (PtRENCs) with {410} high-index facets (HIFs) by an electrochemical method in a choline chloride-urea based deep eutectic solvent. The PtRENCs are used as an efficient catalyst in electrocatalytic nitrogen reduction to ammonia (NH 3 ). Owing to the high density of low-coordinated Pt step sites (HIF structure) and the unique electronic effect of Pt-RE, the as-prepared PtRENCs exhibit an excellent electrocatalytic performance for the nitrogen reduction reaction (NRR) under ambient conditions. The NH 3 yield rate and faradaic efficiency (FE) share the same trend of Pt-La ( r NH 3 : 71.4 μg h −1 μg cat −1 , FE: 35.6%) > Pt-Y ( r NH 3 : 65.2 μg h −1 μg cat −1 , FE: 26.7%) > Pt-Sc ( r NH 3 : 48.5 μg h −1 μg cat −1 , FE: 19%) > Pt ( r NH 3 : 25.8 μg h −1 μg cat −1 , FE: 10.7%). Moreover, the PtRENCs demonstrate high selectivity for N 2 reduction to NH 3 and high stability retaining 90% of the NH 3 yield rate and FE values after 12 h continuous NRR tests. Density functional theory (DFT) calculations indicate that the rate determining step of the NRR process is the formation of N 2 H 2 * from N 2 with the transfer of two proton-coupled electrons, and the upshift of the d-band center boosts the NRR activity by enhancing the bonding strength of reaction intermediates on the high-index faceted Pt-RE (RE = La, Y, Sc) alloying surface. In addition, the introduction of RE (RE = La, Y, Sc) on the Pt step surface can effectively suppress the HER process and provide appropriate sites for the NRR. High-index faceted Pt-RE (RE = La, Y, and Sc) alloys exhibit an excellent electrocatalytic performance for nitrogen reduction to ammonia due to the high density of low-coordinated Pt step sites and the unique electronic effect of Pt-RE.